Análisis del cumplimiento tributarío para la administración de la compañía, de una empresa que se dedica a la comercialización de camarón en la ciudad de Guayaquil durante el período fiscal 2008 - Seminario, I. (2009)
The present project has the main idea to make an analysis of the tributary fulfillment of a company dedicated to the commercialization of shrimp, the conducted study will execute it with respect to the operations conducted by the company during fiscal period 2008, by means of the applications of the effective norm, as it they are Reglamento para la Aplicación de la Ley Orgánica de Régimen Tributario Interno, la Ley Orgánica de Régimen Tributario Interno y el Código Tributario in use of this period. The fulfillment of having formal as far as the presentation of its tributary declarations will be verified, they were analyzed by means of work papers if the tributary activity that exerts the company fulfills the legal and normative dispositions of our country, in addition will detail the evidences of tributary breach, in case there will be, indicating like reference the norm that is breach with its respective article. Recommendations and the respective Report of the analysis will be shown to the Administration of the company to avoid sanctions by any organism of control.